2016
DOI: 10.4172/2471-2701.1000139
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Happiness-Increasing Strategies Between and Within Affective Profiles

Abstract: Background: In a recent study, Schütz and colleagues [1] used the affective profile model (i.e., the combination of peoples' experience of high/low positive/negative affect) to investigate individual differences in intentional happiness-increasing strategies. Here we used a merged larger sample, a person-centered method to create the profiles, and a recent factor validated happiness-increasing strategies scale, to replicate the original findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…By contrast, either the Indonesian or Swedish respondents who mentioned interdependent factors as the matters that made them happy, experienced more subjective well-being than those who reported personal factors as their happiness contributors. Garcia, Schütz, MacDonald, and Archer (2016) could offer an alternative explanation for this issue. In their studies, they found that happier people who scored high on positive affect with either high or low negative affect (i.e., having self-fulfilling or high affective profile) were more likely to choose social affiliation as the happiness-increasing strategy.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, either the Indonesian or Swedish respondents who mentioned interdependent factors as the matters that made them happy, experienced more subjective well-being than those who reported personal factors as their happiness contributors. Garcia, Schütz, MacDonald, and Archer (2016) could offer an alternative explanation for this issue. In their studies, they found that happier people who scored high on positive affect with either high or low negative affect (i.e., having self-fulfilling or high affective profile) were more likely to choose social affiliation as the happiness-increasing strategy.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, researchers (e.g., Garcia, 2012;Garcia, Kerekes, Andersson-Arntén, & Archer, 2012;Garcia, Schütz, & Archer, 2015;Jimmefors et al, 2014) have focused on differences between profiles with regard to personality measures using models such as the Big Five model (Costa & McCrae, 1992) and Cloninger's psychobiological model (Temperament and Character Inventory;Cloninger, Svrakic, & Przybeck, 1993). As hypothesized by these researchers, individuals with a self-fulfilling profile scored high in selfdirectedness, high in cooperativeness, high in persistence, high in extraversion, high in self-regulatory strategies defined as locomotion or a "just-do-it" mentality, and happiness-increasing strategies related to agency (e.g., frequently exercising, active leisure, goal-pursuit), communion (e.g., helping others, receiving help from others), and spirituality (e.g., seek support in faith).…”
mentioning
confidence: 99%
“…Other important differences between the individuals with a self-fulfilling and those with a high affective profile are, for example, that individuals with a high affective profile do not score high in helpful behavior, tolerance toward others, and empathy (i.e., communion and cooperative traits). Individuals with a self-fulfilling profile are, for instance, the only ones who report that they seek support in faith as one strategy in their own pursue of the happy life by guest on April 5, 2016 Downloaded from (Garcia, Schütz, & Archer, 2015;Schütz, Sailer, et al, 2013). However, individuals with a high affective profile score higher than individuals with low negative affect profiles (i.e., low affective and self-destructive) in self-transcendence (i.e., a spiritual trait partially defined as the ability to sense a unity with something bigger than the self; Cloninger, 2004;Garcia, 2012).…”
mentioning
confidence: 99%